A Critical Companion to Old Norse Literary Genre - Bampi, Massimiliano,Sif Ríkharðsdóttir,Larrington, Carolyne (Boydell & Brewer, 2020)
A comprehensive guide to a crucial aspect of Old Norse literature.
Description based on publisher supplied metadata and other sources
Keywords: Altnordisch; Literatur; Literaturgattung